MATRIX -REVOLUTIONS - Fishburne, Laurence, 1961-; Moss, Carrie-Anne, 1970-; Perrineau, Harold; Smith, Jada Pinkett, 1971-; Reeves, Keanu; Weaving, Hugo, 1960-; Wilson, Lambert; Pope, Bill, 1952-; Staenberg, Zach.; Davis, Don, 1957-; Barrett, Kym.; Paterson, Owen.; et al. (Burbank, Calif. : Warner Home Video, 2003)
Neo remains unconscious in the real world, caught in a mysterious subway station that lies between the machine world and the matrix. Bane is still a conduit for Agent Smith, who continues to grow more out of control. Meanwhile, the sentinels are coming dangerously close to Zion. Trinity and Morpheus bargain with The Merovingian to free Neo. Neo, after meeting The Oracle, decides he must leave Zion and go for the machine mainframe. One final battle must ensue, and the future of both races is at stake.
Title from container.
Originally released as a motion picture in 2003.
Director of photography, Bill Pope ; editor, Zach Staenberg ; original music, Don Davis ; costume designer, Kym Barrett ; production designer, Owen Paterson ; visual effects supervisors, John Clinton ... [et al.] ; special effects supervisor, Steve Courtley.
Mary Alice, Monica Bellucci, Ian Bliss, Essie Davis, Laurence Fishburne, Carrie-Anne Moss, Harold Perrineau, Jada Pinkett smith, Keanu Reeves, Hugo Weaving, Lambert Wilson.
MPAA rating: R; for sci-fi violence and brief sexual content.
DVD, fullscreen (1.33:1) presentation.
Keywords: Computer systems -- Drama; Computers -- Drama; Science fiction films; Feature films; Films for the hearing impaired